Natal teeth associated with Riga-Fede disease (Sublingual traumatic disease/traumatic lingual ulceration): A case report and review of literature - Valderrama Iracheta, Lucero; Hernández Trejo, Karla Eugenia; Rosales Solis, Gloria María (2020)
Introduction: Eosinophilic ulcer of the oral mucosa is a rare, self-limiting condition of unknown origin. Ulceration on the ventral surface of the tongue in newborns or infants is more frequently associated with natal or neonatal teeth. Case report: This is a 1-month-old male patient with no significant medical history who was brought to our consultation after presenting an ulcer in the ventral region of the tongue, which increased in size and made breastfeeding difficult. Conclusion: The tooth extraction turned out to be an effective procedure by removing the two incisor neonatal teeth in the lower jaw that the patient had, 2 weeks after extraction the patient evolved favourably without presenting complications.